Chemical parameters and ruminal disappearance of Secale cereale rye forage in different harvest systems with or without fungicide - Heker Junior, Julio Cezar; Neumann, Mikael; Mendes, Marcelo Cruz; de Souza, André Martins; Santos, Leslei Caroline; Pereira e Silva, Emylli; Pontarolo, Giovanna Bobato; de Oliveira, Rômulo Silva; Pinto, Rafaela Guimarães [UNESP] (Universidade Estadual de Londrina, 2020)
The objective of the study was to evaluate the chemical parameters and the ruminal disappearance of dry matter of forage from the rye Secale cereale, cv. Temprano managed in different harvest regimes at the vegetative stage, with or without application of a fungicide based on Fluxapyroxade + Piraclostrobin at the pre-flowering stage. This was a randomized block experimental design and the treatments consisted of evaluating the forage harvested at floury grain stage, as follow, SCSF: no cut at the vegetative stage, no application of fungicide; SCCF: no cut at the vegetative stage with fungicide application; UCSF: one cut at the vegetative stage, no application of fungicide; UCCF: one cut with fungicide application; DCSF: two cuts at the vegetative stage, no fungicide application; DCCF: two cuts with fungicide application. In general, one cut at the vegetative stage and a subsequent cut for ensiling at floury grain stage was the best system used in cv. Temprano, based on the chemical parameters and ruminal disappearance. This system provided a better composition of fiber carbohydrates with lower contents of Acid Detergent Fiber (41.55%) and Lignin (10.79%) after cutting and resulted in a better disappearance rate of dry matter at the rumen level (0.46 %) per hour of exposure, highlighting the cut at the vegetative stage that produced a material with 20.76% Crude Protein and 52.69% Neutral Detergent showing its nutritional quality for use in grazing land or as haylage. The application of fungicide provided significant improvements in the contents of crude protein (8.24% vs 7.23%) and mineral matter (3.02% vs 2.82%) of the plant at the time of ensiling, which generated better dry matter disappearance rates in the rumen.
Parâmetros bromatológicos e desaparecimento ruminal da forragem do centeio Secale cereale em diferentes sistemas de corte com ou sem fungicida
Keywords: Crude protein; Fiber carbohydrates; Pyraclostrobin; Secale cereale